Measurement of the strong coupling constant from inclusive jet production at the Tevatron pp collider. - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2002)
We report a measurement of the strong coupling constant, alpha(s)(MZ), extracted from inclusive jet production in pp collisions at square root[s] = 1800 GeV. The QCD prediction for the evolution of alpha(s) with jet transverse energy ET is tested over the range 40